Overview of the TREC 2024 Tip-of-the-Tongue Track - Arguello, Jaime; Bhargav, Samarth; Diaz, Fernando; Kim, To Eun; He, Yifan; Kanoulas, Evangelos; Mitra, Bhaskar (Text REtrieval Conference (TREC), 2025)
Tip-of-the-tongue (ToT) known-item retrieval involves re-finding an item for which the searcher does not reliably recall an identifier. ToT information requests (or queries) are verbose and tend to include several complex phenomena, making them especially difficult for existing information retrieval systems. The TREC 2024 ToT track focused on a single ad-hoc retrieval task. Participants were provided with training and development data in the movie domain. Conversely, systems were tested on data that combined three domains: movies, celebrities, and landmarks. This year, 6 groups (including the track coordinators) submitted 18 runs.